Parental effects of physiological integration on growth of a clonal herb - Zhang, Li-Min; Zheng, Li-Li; Yu, Fei-Hai (Frontiers in Plant Science, 2025)
Although numerous studies have independently tested the roles of physiological integration and parental effects on the performance of clonal plant species, few have assessed them simultaneously. Moreover, the capacity for physiological integration differs greatly within species of clonal plants. We conducted a greenhouse experiment with eight genotypes of the clonal herb Hydrocotyle verticillata. In the first phase, we either severed or maintained the connections between the original proximal nodes (the basal portion) and the new distal nodes (the apical portion) of each genotype. In the second phase, the ramets in the apical portion produced in the first phase were selected and cultivated, and their connections were subjected to the same severance treatments. In the first phase, the negative effects of severance on the apical portion balanced the positive effects of severance on the basal portion, resulting in no net effect of severance on total mass, leaf mass, stem mass, and ramet number for the whole clone. In the second phase, the effects of parental severance on stem mass of the apical portion of H. verticillata varied among the eight genotypes. Additionally, the positive effect of physiological integration on offspring generations was greater in the apical portion and the whole clone of one genotype when the parental connections were intact than when they were severed, whereas it was greater in the apical portion of another genotype when the parental connections were severed than when they were intact. Our results suggest that clonal parental effects can influence the capacity for physiological integration of offspring generations and that these effects may differ among genotypes within a species.